Nanoporous Titanium Oxynitride Nanotube Metamaterials with Deep Subwavelength Heat Dissipation for Perfect Solar Absorption - Afshar, Morteza; Schirato, Andrea; Mascaretti, Luca; Hejazi, S M Hossein; Shahrezaei, Mahdi; Della Valle, Giuseppe; Fornasiero, Paolo; Kment, Štěpán; Alabastri, Alessandro; Naldoni, Alberto (ACS photonics, 2023)
We report a quasi-unitary broadband absorption over the ultraviolet-visible-near-infrared range in spaced high aspect ratio, nanoporous titanium oxynitride nanotubes, an ideal platform for several photothermal applications. We explain such an efficient light-heat conversion in terms of localized field distribution and heat dissipation within the nanopores, whose sparsity can be controlled during fabrication. The extremely large heat dissipation could not be explained in terms of effective medium theories, which are typically used to describe small geometrical features associated with relatively large optical structures. A fabrication-process-inspired numerical model was developed to describe a realistic space-dependent electric permittivity distribution within the nanotubes. The resulting abrupt optical discontinuities favor electromagnetic dissipation in the deep sub-wavelength domains generated and can explain the large broadband absorption measured in samples with different porosities. The potential application of porous titanium oxynitride nanotubes as solar absorbers was explored by photothermal experiments under moderately concentrated white light (1-12 Suns). These findings suggest potential interest in realizing solar-thermal devices based on such simple and scalable metamaterials.